Combating international terrorism - Sperotto, Federico (Rivista di studi politici internazionali, 2022)
The response to a criminal phenomenon like international terrorism may possibly be articulated in national and international measures, including military intervention on foreign territories, with or without the authorization of the Un Security Council. The response to international terrorism in the form of self-defensive/offensive use of military force beyond national borders, and its legal constraints, is the focus of this work. An analysis of the legality of such a response requires to put together considerations pertaining to inter-State relations and the use of force between States (jus ad bellum), humanitarian law (jus in bello) and human rights.